Ultrastructure of regions containing homologous loci in polytene chromosomes of Drosophila melanogaster and Drosophila subobscura. - Cuenca, J.B.; Galindo, M.I.; Saura, A.O.; Sorsa, V.; de Frutos, R. (Chromosoma, 1998)
We have used a new approach involving in situ hybridisation and electron microscopy to establish ultrastructural homologies between polytene chromosome regions of Drosophila melanogaster and Drosophila subobscura. Twelve probes were chosen to cover all the chromosomal elements: the myospheroid gene, the collagen type IV gene, the collagen-like gene, the w26 homeobox gene, the beta3 tubulin gene, the kinesin heavy chain gene, the tryptophan hydrolase gene, the Hsp82, Hsp22-26 and Hsp23-28, Hsp68, Hsp70 genes and the beta unit of the F0-F1 ATPase gene. Most of these loci were previously undescribed in D. subobscura and imprecisely located in D. melanogaster. We have demonstrated here, by an ultrastructural analysis of each chromosomal region, that homologous genetic loci tend to show a similar ultrastructure in the two species. With a few exceptions, the structural homology extends to the chromosomal regions surrounding the loci. In some cases, however, no structurally recognisable homology can be seen either in the locus or in its flanking regions.